Ministry of Tourism Decree No. 229 of the year 2015 Issued on 3/3/2015 = وزارة السياحة قرار رقم 229 لسنة 2015 صادر بتاريخ 3/3/2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic